Characterization of Gluten-free Bread Prepared From Maize, Rice and Tapioca Flours using the Hydrocolloid Seaweed Agar-Agar - Motrena1, Suse Guerreiro1, Maria JoÃ£o Carvalho1, JoÃ£o Canada1, Nuno Bartolomeu Alvarenga1*, Fernando Cebola Lidon2, Elisa Belga1, PatrÃcia (Recent Research in Science and Technology, 2011)
This work aims to check the rheological, physicochemical and sensory characteristics of gluten-free bread produced with corn, rice and tapioca flours, using the hydrocolloid seaweed agar-agar. Relatively to wheat bread, it was found that the pH was slightly lower in gluten-free bread. In the crust only the brightness remained significantly different between both bread types, but in the kernel, the parameters a*,b* and L* diverge significantly. The toughness as well as the force of penetration and cutting were also significantly different between both bread types. The hedonic evaluation showed that the panellists prefered bread with gluten but the quantitative descriptive analysis did not reveal a clear pattern. The overall assessment pointed that bread with gluten has a greater acceptance by consumers, while gluten-free bread is considered nice in the opinion of the penallists.